Confronting the ‘Arab North’: Interpretations of Slavery and Religion in Southern Sudanese Separatist Resistance - Ylönen, A. (Fluid Networks and Hegemonic Powers in the Western Indian Ocean, 2017)
For centuries, the greater Horn of Africa has been exposed to actors and influences crossing the Red Sea and sailing the Indian Ocean. The extension of these forces has had a profound effect in shaping contemporary societies and states in the sub-region over time. Contemporary Sudan is a fascinating example on how the extension of Islam and the elites-led emphasis on Arab identity has resulted in a society embracing Arab and Muslim culture. These characteristics in the territories that became the heartland of the contemporary Sudanese state translated into the formation of a nationalist governing elite promoting a particular form of Arab culture and interpretation of Islam as the main pillars of national identity for Sudan as a whole. However, the vast territories of contemporary Sudan are culturally highly heterogeneous. This contrasts starkly with the northern political elite’s nation- and state-building project since decolonization, seeking to homogenize society through forced cultural assimilation. Since Sudan’s independence, the state elite imposing Arab culture and Islam has led to varying degrees of direct confrontation with groups that oppose such forced cultural and religious transformation. This chapter reflects on the role of interpretations of slavery and religion in armed opposition and its aftermath in Southern Sudan. It points to the use of particular views of slavery and religion in the two main insurgencies in 1955-1972 and 1983-2005, and reflects on their representations in the Comprehensive Peace Agreement (2005). The chapter argues that these interpretations are related to the Orientalist image of Sudan that connects with the aspirations of southern Sudan’s self-determination, independence, and drift towards East African socio-cultural and Indian Ocean economic space.